[Man or a mouse ; King Copra ; Voter's profile [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
LDP presidential bet Ramon Mitra on his involvement in the coconut levy and the legality of the ranches cast doubt. Danding Cojuangco refutes involvement in the coconut levy. The candidates political machinery as the ultimate decider of the elections.
Man or a mouse (17 min.) -- King Copra (26 min.) -- Voter's profile (17 min.)
VHS.
Keywords: Philippine Coconut Authority -- Corrupt practices; Presidential candidates -- Philippines; Coconut industry -- Corrupt practices; Public opinion -- Philippines